Tarihi Popüler Türk Romanlarında Yüceltilen Bir "Değer" Olarak "Türk Kimliği" - Sağlık, Şaban (Kitabevi, 2002)
The popular historical novels came out carrying a certain aim of promoting Turkish values to the Turkish nation. As one of the main princeples of new Turkish State was nationalism, the process of writing popular "nationalist-minded" novels gathered strength and continutity. Although there has been nunor modification of content, the process of writing popular historical novels has still been going on. These values are exanuned in this study.
The Exalted Turkish ldentity as an Asset in Popular Turkish Novels with Historical Themes
Keywords: Historical Novel; Popular Novel; Turkish Culture; Turkish Values